Verification of the Correlation between the Level of National Competitiveness, Quality of Life and Productivity on the Example of the Developed and Developing Countries of the World - I. Markin, Maksim; V. Shkiotov, Sergei; A. Ugryumova, Marina; N. Savicheva, Anna (International Journal of Psychosocial Rehabilitation, 2020)
There is a certain consensus in the economic literature about the problems of the competitiveness of countries in the global economy—factor productivity determines the country’s competitiveness, its growth rates, and the population’s quality of life. Such an approach became the theoretical foundation of a number of generally recognized competitiveness ratings of countries in the global economy (annual studies of the World Economic Forum, the International Institute for Management Development), which determine, in particular, the attractiveness of an economy for foreign investors. Despite the large array of publications devoted to the analysis and interpretation of the theory of national competitiveness, there remains a significant layer of ideas that have not been subjected to verification and critical analysis. Thus, studies on the analysis of the triad: national competitiveness, labor productivity, and quality of life, taken over a number of years over a wide sample of countries (taking into account a number of quantitative and qualitative indicators), do not exist. The purpose of this work is to study the correlation between the level of national competitiveness, quality of life of the population, and labor productivity, based on the example of 20 developed and developing economies of the world. Based on the data taken from the World Economic Forum reports (2010-2018 period), we verified the hypothesis of the presence of a direct (statistically significant) relationship between the studied indicators using the methods of economic and mathematical modeling. As a result of the study, it was found that the correlation between the economic national competitiveness, labor productivity, and the population’s quality of life in this sample of countries and in the long-term timeframe was confirmed for most of the studied economies.